Predictors of safety and success in minimally invasive surgery for degenerative mitral disease. (5th November 2021) - Bonaros, Nikolaos; Hoefer, Daniel; Oezpeker, Cenk; Gollmann-Tepeköylü, Can; Holfeld, Johannes; Dumfarth, Julia; Kilo, Juliane; Ruttmann-Ulmer, Elfriede; Hangler, Herbert; Grimm, Michael; Mueller, Ludwig
Abstract:  : OBJECTIVES: The aim of this study was to identify predictors of periprocedural success and safety in minimally invasive mitral valve surgery and to determine the impact of pathology localization and repair technique on reoperation-free survival. METHODS: We isolated 686 patients (mean age 60.5, standard deviation 12.3 years, 69.4% male) who underwent surgery for mitral valve prolapse between 2002 and 2020 in a single institution. Patients with concomitant disease, redo or mitral pathology other than degenerative mitral disease were excluded from the analysis. Periprocedural safety was defined as: freedom from perioperative death, myocardial infarction, stroke, use of extracorporeal membrane oxygenation or reoperation for bleeding. Operative success was defined as: successful primary mitral repair without conversion to replacement or to larger thoracic incisions, without residual mitral regurgitation > mild at discharge or reoperation within 30 days. Predictors for perioperative success and safety were identified using univariable and multivariable analyses. The impact of prolapse localization and repair technique on reoperation-free survival was assessed by Cox regression. RESULTS: The mitral repair rate and the need for concomitant tricuspid repair were 94.6% and 16.5%, respectively. Perioperative mortality occurred in 5 patients (0.7%). The criteria for perioperative safety and success were met in 646/686 (94.2%) and 648/686 (94.5%) patients, respectively. The absence of tricuspid disease requiring repair was the only independent predictor of safety in this cohort [hazard ratio (HR) 0.460 (0.225–0.941), P  = 0.033]. The only independent predictor of operative success was the use of chordal replacement [0.27 (0.09–0.83), P  = 0.022]. Reoperation-free survival was 98.5%, 94.5% and 86.9% at 1, 5 and 10 years, respectively. Posterior leaflet pathology demonstrated a higher reoperation-free survival as compared to other localizations (log-rank P  = 0.002). The localization of leaflet pathology but not the repair method was an independent predictor for reoperation-free survival (HR 1.455, 95% confidence interval 1.098–1.930; P  = 0.009). CONCLUSIONS: In minimally invasive mitral surgery for degenerative disease, chordal replacement yields higher rates of periprocedural success than leaflet resection. Posterior leaflet pathology is an independent predictor of reoperation-free survival. Abstract : The feasibility of minimally invasive mitral valve surgery (MIMVS) for the treatment of degenerative mitral disease has been well established [1].